The Role Of Technology In Human Resource Management To Improve MSMEs In Indonesia - Fazriyani, Fanesha; Prahiawan, Wawan (LPPM Universitas Banten jaya, 2024)
This study aims to determine the role of technology in human resource management to improve MSMEs in Indonesia. The approach used in this research is descriptive qualitative. Data collection techniques in this study by collecting data from books or journals. The type of data used is secondary data obtained from the Databoks website. Katadata.co.id and data from the Central Statistics Agency (BPS). The results of this study explain that technology plays an important role in human resource development and provides several benefits for MSMEs in terms of product development, due to the many online marketing features available, from product availability to the payment process. The technologies used in human resource management are HRIS, ATS and LMS. The use of technology in the worker selection process is a common choice in human resource management to find a worker who is in accordance with what the company needs.